FAKTOR KESIAPAN DAN ADOPSI TEKNOLOGI INFORMASI DALAM KONTEKS TEKNOLOGI SERTA LINGKUNGAN PADA UMKM DI JAKARTA - Asrul Sani; Ninuk Wiliani (LPPM Nusa Mandiri, 2019)
Use of information technology in general is very important for the development of the organization. Likewise, if the development of information technology can be applied to the small and medium business sector, so that it can increase the selling value of the sector. This research was conducted to answer the readiness of the SMEs sector in adopting information technology developments in business management. In this case the researcher develops the research model by adopting the technology readiness model and information technology adoption model in the context of technology and environment, combining and adjusting it according to the development of SMEs in Jakarta. This quantitative study involved 67 samples from MSME workers. Data was processed and analyzed using the PLS-SEM method using SmartPLS 2.0 software. The study also explained the results of the readiness factor which has a significant relationship to the utilization of information technology in SMEs in Jakarta